Os papéis urbanos nas pequenas cidades da região da Quarta Colônia - RS - Spolaor, Silvane (2010)
This present study discusses Quarta Colônia Region (Fourth Colony Region), localized in central area of Rio Grande do Sul state, Brazil, near Santa Maria/RS. Quarta Colônia has a population of about 63 thousand habitants which represents 0,6% of the total population of Rio Grande do Sul. The ancient Quarta Colônia of Italian immigration, named Silveira Martins, was founded in 1875, completing therefore the initial basic centre of Italian immigration in Rio Grande do Sul. The occupation of this region had as initial impulse the Italian immigration. Nowadays Quarta Colônia Region is composed by nine towns: Agudo, Dona Francisca, Faxinal do Soturno, Ivorá, Nova Palma, Pinhal Grande, Restinga Seca, São João do Polêsine e Silveira Martins. Agudo (Germain immigration) and Restinga Seca are added to the region for political and economic reasons. This Master work was developed using the coverage area of Plano Diretor Ambiental da Região da Quarta Colônia (Environment Director Plan of Forth Colony Region), making use of its data and information. The city of Silveira Martins, even known as the place of origin of Italian immigration, is not included in the planning proposed by Plano Diretor Ambiental because of political and economic reasons. In Quarta Colônia region the picturesque scenery, that includes landscapes characterized by rugged relief, by old buildings and by the way of life based on traditions and beliefs, as well as close ties, is reference for a review of the way of life, of learning and doing of their small towns. Among the general haracteristics of these studied towns stand out: predominance of residential function; little commercial and service diversity; interpersonal relationships are very narrow, with high degree of knowledge among citizens; squares are meeting places of population and also are places of recreation; shifts within the city are made on foot, due to short distances. In these towns the religiosity is very present, fact that can be confirmed by the significant presence of churches; the existence of an urban way of life, co-existing with some rural way of life and finally, the existing tranquility and little problems related to lack of security. In this context, the towns of Quarta Colônia region have natural potentialities, talents and aptitudes still unexplored which may add in its socioeconomic growth, supported by actions of public officials and public policy.